PENGARUH EKSTENSIFIKASI PAJAK, KEPATUHAN WAJIB PAJAK, PEMERIKSAAN PAJAK, PENAGIHAN PAJAK DAN SURAT PAKSA PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI DI KPP PRATAMA SOLOK - hudany, Reida wulan; Hasan, Amir; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect caused by the variable tax extension, tax compliance, tax audits, tax collection and tax forced letter with personal income tax revenue.This study use of probability sampling, while is a technique pliers provide equal opportunity for each element (member) of the population to be elected as members of the sample. Data collection techniques in this study is a form of literature study and documentation. While the data analysis technique used is multiple regression analysis were processed with SPSS version 17 for Windows. From the results of the testing that has been done, partial regression test (t test) showed that tax entension and tax audits doest not affect on the variable personal income income tax revenue with significant value of 0,147 and 0,146. While tax compliance, tax collection and tax forced letter effect on the variable personal income tax revenue with signifikant value of 0,012, 0,037 and 0,035. The magnitude of the effect caused by Adjusted R2by four variables together against the dependent variable 44.9%, while the remaining 55.1% is influenced by other variables not examined in this study.Keywords : tax extension, tax compliance, tax audits, tax collection and tax forced letter